2016
DOI: 10.1016/j.canlet.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Statin derivatives as therapeutic agents for castration-resistant prostate cancer

Abstract: Despite recent advances in modern medicine, castration-resistant prostate cancer remains an incurable disease. Subpopulations of prostate cancer cells develop castration-resistance by obtaining the complete steroidogenic ability to synthesize androgens from cholesterol. Statin derivatives, such as simvastatin, inhibit cholesterol biosynthesis and may reduce prostate cancer incidence as well as progression to advanced, metastatic phenotype. In this study, we demonstrate novel simvastatin-related molecules SVA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…In this context, the majority of data support that statin use is associated with reduced risk of PCa . Statin derivatives showed reduced tumorigenicity in androgen receptor positive and negative PCa cells . Inhibition of ABCG4 levels by simvastatin resulted in the enhanced accumulation of intracellular Dox.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the majority of data support that statin use is associated with reduced risk of PCa . Statin derivatives showed reduced tumorigenicity in androgen receptor positive and negative PCa cells . Inhibition of ABCG4 levels by simvastatin resulted in the enhanced accumulation of intracellular Dox.…”
Section: Discussionmentioning
confidence: 99%
“…41 Statin derivatives showed reduced tumorigenicity in androgen receptor positive and negative PCa cells. 42 intracellular Dox. In agreement with this, we have earlier shown that statins by augmenting GSH dependent antioxidant mechanisms inhibit breast cancer proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Cell migration was assessed via Boyden Chamber transwell assay as described previously [31,37]. Cells were plated at a density of 5 × 10 4 cells into the upper chamber of 24-well plate transwell inserts and allowed to migrate for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were harvested via trypsinization and live cell numbers were counted by Trypan Blue dye exclusion assay using a Cellometer Auto T4 Image-based cell counter (Nexcelom, MA, USA) [7,37]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation